Multimedialna wizualizacja modeli symulacyjnych dla potrzeb zarządzania - Łatuszyńska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Development of multimedia techniques influences considerably the manner of visualization of results generated by simulation models. The article presents the possibilities of introducing the results of simulation experiments with the use of several integrated means (i.e. text, graphic, animation, sound and video clip) on the example of models created in convention of system dynamics method. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 175-185